Studi Deskriptif Nilai Moral Dalam Cerita Rakyat "Singaran Pati Raja Sungai Hitam” Sebagai Sumber Belajar - Permatasari, Serli Yulia; Muktadir, Abdul (JURIDIKDAS, 2024)
This study aims to describe the moral values contained in the Bengkulu folklore "Singaran Pati King Of Black River" and describe the suitability of the story as a learning resource for fourth grade students at SDN 105 Bengkulu City. This type of research is descriptive qualitative research using discourse content analysis method. The research subject was the Bengkulu folklore book "Singaran Pati King Of Black River". The main instrument in this research is the researcher herself while the supporting instrument is the Bengkulu folklore analysis table. Data is collected by reading, tagging, collecting, and entering into data analysis tables. The results showed that the Bengkulu folklore “Singaran Pati King Of Black River” includes all moral values according to the theory of Nurgiyantoro and Jayanti, namely there are 25 dimensions of moral values spread over four moral value relationships. The twenty-five moral values are divided into 11 moral values of human relations with oneself, 10 moral values of human relations with other human beings, 2 moral values of human relations with nature and 2 moral values of human relations with God. In addition, the Bengkulu folklore book “Singaran Pati King Of Black River” is suitable to be used as a learning resource for elementary school students because this storybook uses child-friendly language, in accordance with the characteristics of children's literature and contains a lot of positive moral values that can be applied by students, both in the home, school and community environment.